OFICINAS TERAPÊUTICAS DE CONTOS COM CRIANÇAS EM SITUAÇÃO DE ABRIGAMENTO - Schonardie, Elisiane F.; Tolfo, Taíse F.; Tedeschi, Vandriane; Librelotto, Maria I. B.; Junges, Marluce (Salão do Conhecimento, 2013)
Resumo